Effect of proteolytic enzyme bromelain on pain and swelling after removal of third molars - Singh, Tejpal (J Int Soc Prev Community Dent, 2016)
AIMS AND OBJECTIVES: To evaluate the effect of bromelain on pain and swelling after surgical removal of third molars. MATERIALS AND METHODS: A prospective randomized clinical study was conducted among 40 patients requiring surgical removal of impacted mandibular third molars. All the impacted molars were surgically removed, and the patients were administered bromelain along with amoxicillin. Patients were recalled on day 1, day 3, and day 7 for postoperative pain assessment using visual analogue scale (VAS) and postoperative swelling assessment using facial reference points tragus and pogonion. VAS score was statistically analyzed using repeated analysis of variance with post-hoc Bonferroni test postoperatively on day 1, day 3, and day 7 using the Statistical Package for the Social Sciences software version 14. RESULTS: Out of the total 40 patients, bromelain was effective in 28 (70%) patients. In these patients, there was reduction in swelling and pain after taking bromelain. CONCLUSION: Bromelain can be used as a successful oral enzyme therapy for oral surgery patients, especially after removal of impacted third molars.